Traumatic myiasis by Wohlfahrtia magnifica in sheep flocks from southeastern Spain: prevalence and risk factors. Issue 1 (21st September 2021) - Remesar, S.; Otero, J. L.; Panadero, R.; Díez‐Baños, P.; Díaz, P.; García‐Díos, D.; Martínez‐Calabuig, N.; Morrondo, M. P.; Alonso, F.; López, C.
Abstract: Wohlfahrtia magnifica (Diptera: Sarcophagidae) is an obligate myiasis‐causing fly of livestock that is widely distributed throughout the Mediterranean basin. A total of 73 683 sheep from 122 flocks in Albacete Province (southeastern [SE] Spain) were examined to detect active traumatic myiasis. The influence of several individual and flock factors on the prevalence was also assessed. The overall flock prevalence of traumatic myiasis was 95.9%, with an individual prevalence of 7.1%. Wohlfahrtia magnifica was identified in all of the positive animals except one that was infested by Lucilia sericata (Diptera: Calliphoridae). Adults of both genders showed a higher risk of infestation than juveniles, whereas males of all ages displayed an increased risk of infestation than females of all ages; the existence of a lambing building on the farm, poor husbandry facilities and the location area were also identified as risk factors. Prevalence was highest in the summer, and the fly season lasted from March to November. Genitalia were the main location of infestation in males (94.4%) and females (76.3%). Our results reveal that traumatic myiasis by W . magnifica is widespread in southeastern Spain, hence preventive measures minimizing the attractiveness of sheep to gravid flies are necessary to avoid health and welfare problems and significant production losses in sheep flocks. Abstract : Traumatic myiasis is highly prevalent in flocks from southeastern Spain; Wohlfahrtia magnifica was identified in all of the positive animals except one that was infested by Lucilia sericata . Adults and males showed higher infestation risk than juveniles and females, respectively; the existence of lambing buildings, poor husbandry facilities and the location area were also identified as risk factors. Genitalia were the main location of infestation in males and females.